Social Construction of the Tradition of Cooking Vegetable Lodeh 7 Rupa as a Repellent to the Covid 19 Pandemic: A Study in Baran Keniten Village, Mojo District, Kediri Regency - Pangestuti, Ratna Dewi (Jurnal Multidisiplin Madani, 2023)
Culture is a human product, which then binds human actions into a single unit. As is the case, the people in Baran Village are still bound by a culture in their social reality. People in Baran Village interpret that the 7-form vegetable dish can be a disaster repellent. Thus, this research aims to dismantle the social construction that has been adopted by the people of Baran Village, in an effort to prevent the co-19 pandemic. This research uses a descriptive qualitative method with Alfred Schutz's phenomenological approach. Meanwhile, this research uses the theory of Peter L. Berger and Thomas Luckman in unmasking social construction. The results of this study show that the community constructs vegetable lodeh 7 rupa through its social reality, such as cooking and eating vegetable lodeh 7 rupa as a daily dish. More than that, the meaning implied by the advice of elders in each of the 7 raw materials is interpreted through actions such as worship, staying at home, and maintaining health as an effort to harmonize themselves from the disturbed natural balance